2018
DOI: 10.1039/c8gc01797b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal azide–alkene cycloaddition reactions: straightforward multi-gram access to Δ2-1,2,3-triazolines in deep eutectic solvents

Abstract: Straightforward preparation of 1,2,3-triazolines in Deep Eutectic Solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 92 publications
2
23
0
Order By: Relevance
“…Furthermore, the reaction times can be dramatically reduced in DES since higher temperatures than in the previously reported solvents (typically MeOH or toluene) are now possible. This is most probably due to a stabilising effect of the solvent on the transient triazolines, which minimises undesired decomposition and promotes the formation of cycloadducts . Most remarkably, previous reports in organic solvents used basic conditions to promote the formation of pyrazolines, but in contrast, our DFT calculations points to formal acidic media (a combination of H + and Cl − ) as key for this reaction in DES.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Furthermore, the reaction times can be dramatically reduced in DES since higher temperatures than in the previously reported solvents (typically MeOH or toluene) are now possible. This is most probably due to a stabilising effect of the solvent on the transient triazolines, which minimises undesired decomposition and promotes the formation of cycloadducts . Most remarkably, previous reports in organic solvents used basic conditions to promote the formation of pyrazolines, but in contrast, our DFT calculations points to formal acidic media (a combination of H + and Cl − ) as key for this reaction in DES.…”
Section: Resultsmentioning
confidence: 61%
“…We previously reported that such transition states could lead to the formation of either an aziridine or an imine derivative. An alternative retro‐cycloaddition to a diazo compound and an imine ( TS2 3 , Scheme ) is a non‐productive but non‐competitive pathway (ΔΔG ≠ 333 =31.3 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, Sebest and co-workers developed a synthetic procedure to form 1,2,3-triazolines 76 by direct 1,3-dipolar azide-alkene cycloaddition reaction in a series of DESs (Scheme 14) [59].…”
Section: R R 1 Yield (%)mentioning
confidence: 99%